Chemical Stability of Prebiotics and Synbiotics in Pharmaceutical Formulations (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Prebiotics and synbiotics have gained considerable attention in pharmaceutical research due to their potential to improve gut microbiota, enhance immune function, and promote overall health. Prebiotics are non-digestible carbohydrates that selectively stimulate the growth of beneficial intestinal microorganisms, while synbiotics combine prebiotics with probiotics to improve their survival and therapeutic efficacy. The effectiveness of these formulations is closely associated with their chemical stability during manufacturing, storage, and administration.Several environmental and formulation-related factors, including temperature, moisture, pH, oxygen, light, and processing conditions, can influence the chemical stability of prebiotics such as inulin, fructooligosaccharides (FOS), and galactooligosaccharides (GOS). Degradation of these compounds may reduce their functional properties and negatively affect the viability of probiotics in synbiotic formulations. Therefore, maintaining the stability of both components is essential for ensuring product quality and therapeutic performance.Various formulation strategies, including microencapsulation, lyophilization, incorporation of protective excipients, and the use of moisture-resistant packaging, have been employed to enhance the stability and shelf life of these products. Analytical techniques such as High-Performance Liquid Chromatography (HPLC), Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA) play a crucial role in evaluating chemical integrity, identifying degradation products, and ensuring quality control. A comprehensive understanding of the factors affecting chemical stability and the application of suitable analytical and formulation approaches are essential for developing stable, safe, and effective prebiotic and synbiotic pharmaceutical formulations. These advancements support the growing application of functional ingredients in modern drug development and healthcare.
Keywords: Prebiotics; Synbiotics; Chemical Stability; Pharmaceutical Formulations; HPLC; Quality Control